Electrospun biopolyesters as drug screening platforms for corneal keratocytes - Azari, P.; Luan, N.S.; Gan, S.N.; Yahya, R.; Wong, C.S.; Chua, K.H.; Pingguan-Murphy, Belinda (2015)
In vitro drug screening techniques provide rapid and easy to analyze data, while saving a lot of animals from being sacrificed. An important part of any in vitro drug screening platform is a biomaterial which promotes cell growth and proliferation. The potential of electrospun scaffolds made of polyhydroxybutyrate (PHB), poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHBV), and polycaprolactone (PCL) were studied to serve as drug screening platform for corneal keratocyte tissues. The results showed that the proliferation rate was slightly higher for PCL and PHBV on day 7. Gene expression results showed that PCL was the best in maintaining keratocyte genes. GRAPHICS .